Severe Complications in Testicular Germ Cell Tumors: The Choriocarcinoma Syndrome - Rejlekova, Katarina; Cursano, Maria C.; De Giorgi, Ugo; Mego, Michal (Frontiers in Endocrinology, 2019)
Testicular germ cell tumors (TGCTs) represent the most common solid tumor in young men and is a model of curable cancer. Effectiveness of cisplatin-based chemotherapy insure for more than 95% of patients’ five-year survival rate. However, some high-risk patients with very advanced disease develop shortly after beginning of systemic chemotherapy choriocarcinoma syndrome (CS) connected with acute respiratory failure with poor prognosis and high mortality rate. CS was first described as a syndrome with hemorrhage from metastatic sites in patients with TGCTs with significantly high choriogonadotropin level. Acute hemorrhage to lung metastases is typical, but hemorrhage from any metastatic site can occur. Patognomic of choriocarcinoma cells is invasion of small blood vessels within CS. Incidence of CS in patients with TGCTs are not well defined and can vary between the world. To date, there is few case reports and small retrospective series reporting connection between systemic chemotherapy and development of CS in metastatic TGCTs. It is supposed that CS is triggered by massive tumor cell lysis as a result of chemotherapy and cytokine release afterwards aggravated with alveolar hemorrhage. This can lead to consecutive superinfection, furthered with neutropenia after chemotherapy, acute respiratory distress syndrome raising to systemic inflammatory response directing to multiorgan failure and death. Reasonable effective approach in patients with extensive disease could be shortened course of chemotherapy as well as reduction of dosage in induction chemotherapy before full-dose chemotherapeutical regimen, however, current data regarding optimal treatment approach are limited. Patients referral to tertiary centers and administration of induction chemotherapy in intensive care unit setting could further improve treatment outcome.